Energetic, economic and environmental benefits of utilizing the ice thermal storage systems for office building applications - Rismanchi, Behzad; Saidur, Rahman; Masjuki, Haji Hassan; Mahlia, Teuku Meurah Indra (Elsevier, 2012)
In recent decades, around the world, a huge amount of daytime peak power has been shifted to the off-peak hours by using different types of thermal energy storage systems. However, the contribution of these systems in Malaysia is still minor in comparison with their potential. Therefore, the feasibility and potentiality of employing ice thermal storage (ITS) systems for office building cooling applications is studied to investigate their economical and environmental benefits. The air conditioning systems in Malaysia are considered as the major energy consumers in office buildings with around 57 share. The economical analysis of the cost benefits is carried out for a system including chiller and storage system. The installation costs are mainly dominated by the total system capacity; hence the study was conducted for a range of 100-2000 tons of refrigeration (TR) (352-7034 kW) for two storage strategy of full storage and load levelling storage strategy. The results indicate that considering the special off-peak tariff rate of 0.06/kWh for the total system capacities of 500 and 1500 TR (1758 kW and 5275 kW), the annual cost saving varies from 230,000 to 700,000 and from 65,000 to 190,000 for full storage and load levelling storage strategy, respectively. The overall results show that the full storage strategy can reduce the annual costs of the air conditioning system by up to 35 while this reduction is limited to around 8 for a load levelling strategy. The comparison study reveals that for the full storage strategy the payback period varies between 3 and 6 years while the payback period for the load levelling strategy varies between 1 and 3 years. It was concluded that the ITS system can play a vital role in consuming the natural resources in a more efficient, economical and environmentally benign way by changing the electricity consumption pattern to overcome the disparity between energy generation and energy demand.